The Sun,17 Julai 2007 - Tham, Cindy (Sun Media Corp.Sdn.Bhd., 2007)
"Malays, Chinese, Indians and other races that wish to be loyal, live togather, defend the nation and work together, live in harmony, because the situation in this country is deferent from other countries in the world. Because of this, one race cannot tke everything for itself. In order to set up an independent government, we must comprimise and make ascrifices.